Lulu and the brontosaurus - Viorst, Judith (Lulu - Viorst, 2010)
Lulu's parents refuse to give in when she demands a brontosaurus for her birthday and so she sets out to find her own, but while the brontosaurus she finally meets approves of pets, he does not intend to be Lulu's.